2006
DOI: 10.1161/01.str.0000198845.79254.0f
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Onset Time Using Sodium MRI in Rat Focal Cerebral Ischemia

Abstract: Background and Purpose-Thrombolytic therapy with intravenous tPA must be administered within 3 hours after stroke onset. However, stroke onset time cannot be established in 20% to 45% of potential patients. We propose that the rate of increase of the brain concentration of sodium ([Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 38 publications
8
84
1
Order By: Relevance
“…However, equally important, the model allows for the rapid transfer of the rat into the MRI system after the surgery is performed, allowing for the acquisition of TSC time course data from as early as 30 minutes after stroke onset time. Indeed, in the current study, the first data point after MCAO was sampled significantly earlier than in previously reported MCAO rat studies, where delays of between 2 to 4 hours have been reported [6,22]. (although the former study did report a delay of 1.1 hour for one rat) As a result, the evolution of the TSC in the crucial early phase after MCAO was not measured which may have lead to erroneous conclusions about regional TSC changes in these studies.…”
Section: Discussionmentioning
confidence: 72%
“…However, equally important, the model allows for the rapid transfer of the rat into the MRI system after the surgery is performed, allowing for the acquisition of TSC time course data from as early as 30 minutes after stroke onset time. Indeed, in the current study, the first data point after MCAO was sampled significantly earlier than in previously reported MCAO rat studies, where delays of between 2 to 4 hours have been reported [6,22]. (although the former study did report a delay of 1.1 hour for one rat) As a result, the evolution of the TSC in the crucial early phase after MCAO was not measured which may have lead to erroneous conclusions about regional TSC changes in these studies.…”
Section: Discussionmentioning
confidence: 72%
“…In regard to the hypothetical mode of operation of NCX3 during stroke, it should be underlined that the region of maximum [Na ϩ ] increase, measured in the brain by MRI, corresponds to the ischemic core region (Jones et al, 2006). Although MRI detection does not allow discrimination between intracellular and extracellular Na ϩ localization, it is plausible to suggest that, in the ischemic core, NCX3, as a result of intracellular Na ϩ overload, could be forced to operate in the reverse mode as a Na ϩ efflux-Ca 2ϩ influx pathway (Amoroso et al, 2000;Annunziato et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, whereas the function of NCX under physiological conditions has been determined, its function under anoxic conditions is still unknown. In fact, in the early phase of neuronal anoxic insult, the initial blockade of Na ϩ -K ϩ ATPase increases [Na ϩ ] i (Amoroso et al, 1997;Jones et al, 2006), which, in turn, elicits a profound Ca 2ϩ entry through the activation of the NCX reverse mode of operation. Although the reverse mode of operation elicits an increase in [Ca 2ϩ ] i , its effect could be beneficial for neurons, because it contributes to a decrease in [Na ϩ ] i overload, thus preventing cell swelling and death.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing static magnetic field strengths and stronger, faster and more accurately controllable gradient and acquisition hardware, 23 Na Magnetic Resonance Imaging ( 23 Na-MRI) has become a promising technique to investigate diseased tissue states non-invasively in pre-clinical models of disease [1][2][3][4]. The potential diagnostic benefits of 23 Na-MR imaging have recently been demonstrated for common pathological conditions such as tumor [5,6], stroke [7][8][9], Alzheimer disease [10], paramyotonia [11], arthritis [12], multiple sclerosis [13] and functional renal imaging [14] in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging of the rat brain poses an additional challenge, due to the small voxel sizes typically required (in the μl range) to achieve the spatial resolution necessary to identify common brain structures such as the cortex and the subcortex in rodent stroke models. As a result, deriving a meaningful conclusion from such low resolution data in recently published studies has proved difficult [1,18,19]. Attempts have been made to improve the achievable SNR in 23 Na-MRI by developing optimal radiofrequency resonators [20], although it is clear that higher spatial-temporal resolution is required if 23 Na-MRI is to realize its considerable potential in in vivo studies.…”
Section: Introductionmentioning
confidence: 99%